Showing off - Mlynowski, Sarah; Myracle, Lauren, 1969-; Jenkins, Emily, 1967- (Mlynowski, Sarah. Upside-down magic, 2017)
The Dunwiddle Magic School (fifth to eighth grade) is intended for children whose magic is "upside-down" like Dory (who turns into a combination of a kitten and dragon) and Pepper (whose uncontrollable "fiercing" terrifies everyone around her)--so the Show Off, where fifth grade students are supposed to showcase their skills, does not really seem like a good idea.